The Effect of Leadership Competency Units on Organizational Effectiveness in Ethiopia: The Case of Federal Public Sector - Sherkabu, Desalegn; Zelalem, Fisseha (African Journal of Leadership and Development, 2023)
This study aims at investigating the effect of the major leadership competency units on organizational effectiveness in the Ethiopian Federal Public Service. The study participated 1,272 public servants from a sample of nineteen entities chosen on simple random basis of the lottery method. A five-point Likert type scale survey with all the items having a well over .75 Cronbach’s alpha coefficient, FGD’s and document analyses were employed. Quantitative-qualitative mixed; cross-sectional survey study design was used. The quantitative data was analyzed using descriptive and inferential statistics techniques of multiple linear regression method. The qualitative data was analyzed thematically. The result of the study showed that the overall leadership competency units have significant effect on organizational effectiveness. It was found that the value of the determination coefficient (R2) 0.52 indicating that the Ethiopian Public Sector effectiveness can be explained by intrapersonal, interpersonal, technical, direction setting, and career competencies to this level. Other factors not studied in this research contributed 48 % for the public service organizational effectiveness. While the descriptive analyses depicted that there is a slightly higher than average rating between 3.18 and 3.62 mean scores in all the six independent and the dependent variable; the qualitative data results aligned more to the regression analyses implying that the competency units identified positively explain the organizational effectiveness. Finally, further research should be conducted to investigate the other factors (48%) that influence leadership competences for the Ethiopian public sector.